Study reporting quality among interventions to reduce antibiotic use is a barrier to evidence-informed policymaking on antimicrobial resistance: systematic review. (16th January 2020) - Rogers Van Katwyk, S; Grimshaw, J M; Nkangu, M; Mendelson, M; Taljaard, M; Hoffman, S J
Abstract: Background: Countries are currently seeking evidence-informed policy options to address antimicrobial resistance (AMR). While rigorous evaluations of AMR interventions are the ideal, they are far from the current reality. Additionally, poor reporting and documentation of AMR interventions impede efforts to use evidence to inform future evaluations and policy interventions. Objectives: To critically evaluate reporting quality gaps in AMR intervention research. Methods: To evaluate the reporting quality of studies, we conducted a descriptive synthesis and comparative analysis of studies that were included in a recent systematic review of government policy interventions aiming to reduce human antimicrobial use. Reporting quality was assessed using the SQUIRE 2.0 checklist of 18 items for reporting system-level interventions to improve healthcare. Two reviewers independently applied the checklist to 66 studies identified in the systematic review. Results: None of the studies included complete information on all 18 SQUIRE items (median score = 10, IQR = 8–11). Reporting quality varied across SQUIRE items, with 3% to 100% of studies reporting the recommended information for each SQUIRE item. Only 20% of studies reported the elements of the intervention in sufficient detail for replication and only 24% reported the mechanism through which the intervention was expected to work. Conclusions: Gaps in the reporting of impact evaluations pose challenges for interpreting and replicating study results. Failure to improve reporting practice of policy evaluations is likely to impede efforts to tackle the growing health, social and economic threats posed by AMR.